Iraq : Use of Fund Resources-Request for Emergency Post-Conflict Assistance. (IMF Staff Country Reports; Country Report, 2004)
This paper reviews Iraq's Request for Emergency Post-Conflict Assistance (EPCA). The authorities' main goals under the EPCA-supported program are to improve the general welfare of the Iraqi people and address Iraq's external debt problem. The authorities' program is to be underpinned by a prudent fiscal policy that aims to limit spending to available government revenues and external resources, the use of the exchange rate to anchor inflation expectations, and the planning and undertaking of key structural reforms to transform Iraq into a market economy.